LIVERWORTS AND HORNWORTS OF KAS PLATEAU - S. A. BAGAWAN,; B. A. KORE, (The Bioscan, 2012)
This paper reports for the first time, distribution of liverworts and hornworts of Kas plateau. It includes 20 species belonging to 12 genera, 8 families and 3 orders. Riccia, Cythodium, Plagiochasma, Astrella, Fossombronia, Solenostoma, Anthoceros and Notothylas were very common while Cryptometrium and Porella were very rare genera in the study area. This diversity needs to be conserved against anthropogenic pressure.